Book of mathematic education (bom-e) : perbedaan peningkatan kemampuan komunikasi matematis siswa - Moh Andi Bahtiar; Evan Farhan Wahyu Puadi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
The purpose of this research is to know if there any difference and improvement of students mathematic communication ability by using learning models Teams Games Tournaments that modified by Gallery Walk between the students who used with the students who didn’t used a media device Book of Mathematic Education (BOM-E). Research method that had been used in this research is quantitative description with experimental method. The population of this research is the students of SMK Yamsik Kuningan Class XI as many as 110 students with the total of sample is 55 students. The experiment class is the students who used learning media device Book of Mathematic Education (BOM-E) and the control class is the students who didn’t used learning media device Book of Mathematic Education (BOM-E). The research intrument that had been used by this research is test instrument in the form of pretest and posttest essay questions. Data analysis techniques used Normality test as a prerequisite test, because there is a data that are not normally distributed so the data processing by non-parametric statistics used Kruskal-Wallis H Test. The result of this research showed that in Kruskal-Wallis H Test produces H values as bis as 30,3030 with Chi Square value as bis as 3,8415 and that means there is a differences of improvements in mathematical communication ability. So it can be concluded that in the application of mathematics learning media device Book of Mathematic of Education (BOM-E) has an influence on the differences in the improvement of students mathematical communication ability where the students who used learning media device Book of Mathematic Education (BOM-E) have a significant increase compared to the students who didn’t used learning media device Book of Mathematic Educationn (BOM-E).